2017
DOI: 10.1007/s00441-017-2749-y
|View full text |Cite
|
Sign up to set email alerts
|

iPS cells in the study of PD molecular pathogenesis

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease and its pathogenic mechanisms are poorly understood. The majority of PD cases are sporadic but a number of genes are associated with familial PD. Sporadic and familial PD have many molecular and cellular features in common, suggesting some shared pathogenic mechanisms. Induced pluripotent stem cells (iPSCs) have been derived from patients harboring a range of different mutations of PD-associated genes. PD patient-derived iPSCs have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 179 publications
(301 reference statements)
0
26
0
Order By: Relevance
“…Among them, SNCA, LRRK2, and VPS35 are associated with PD in autosomal dominant forms, and PINK1 and PARK2 are associated with PD in autosomal recessive forms. In addition, genome-wide association studies have found that plenty of variants in glucosidase beta acid (GBA) are risk factors for PD [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, SNCA, LRRK2, and VPS35 are associated with PD in autosomal dominant forms, and PINK1 and PARK2 are associated with PD in autosomal recessive forms. In addition, genome-wide association studies have found that plenty of variants in glucosidase beta acid (GBA) are risk factors for PD [5].…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, the molecular mechanisms of PD involve oxidative stress, mitochondrial dysfunction, autophagy, axonal transport, and neuroinflammation [5]. Increased oxidative stress products can damage macromolecules and cause mitochondrial dysfunction, which subsequently triggers mitochondrial autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Duplication, triplication, and rare mutations (A53T, A30P, E46K, H50Q, G51D, A53E) in the SNCA gene encoding the α-syn protein have been found in families with dominantly-inherited PD and are associated with early-onset forms of PD, with an amplification of α-syn aggregation [2][3][4][5]. The A53T [6], A30P [7] and E46K [8] substitutions have been the most studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of these different differentiation protocols has facilitated research on many neurological diseases using iPSCs. The current state of this research has been recently reviewed for a range of diseases (Gibbs et al, 2018;Inak et al, 2017;McKinney, 2017;Poon et al, 2017;Tamburini and Li, 2017) including Parkinson's disease (Cobb et al, 2018;Singh Dolt et al, 2017), Alzheimer's disease (Arber et al, 2017;Robbins and Price, 2017), amytrophic lateral sclerosis and frontotemporal dementia (Guo et al, 2017;Preza et al, 2016), Huntington's disease (Tousley and Kegel-Gleason, 2016), childhood neurological diseases (Barral and Kurian, 2016;Santos and Tiscornia, 2017), and psychiatric disorders (Adegbola et al, 2017;Watmuff et al, 2017). These reviews cover differentiation of specific neuronal subtypes and relevant disease phenotypes observed in these cells, therefore these topics will not be covered here.…”
Section: Introductionmentioning
confidence: 99%